Salt-tolerance mechanisms in quinoa Is glycinebetaine the missing piece of the puzzle? - Olmos, E (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2023 The Authors. Published by Elsevier Masson SAS.. All rights reserved.